A bimetallic MOF@graphene oxide composite as an efficient bifunctional oxygen electrocatalyst for rechargeable Zn–air batteries. Issue 17 (22nd April 2020) - Xiao, Yao; Guo, Beibei; Zhang, Jing; Hu, Chun; Ma, Ruguang; Wang, Deyi; Wang, Jiacheng
Abstract : A bimetallic ZnCo-ZIF@graphene oxide (ZnCo-ZIF@GO) composite was synthesized via an in situ growth strategy. As the air cathode of Zn–air batteries, ZnCo-ZIF@GO showed good charge/discharge performance and long-term stability. Abstract : The development of low-cost bifunctional catalysts for replacing precious metal Pt-group electrocatalysts is highly desirable but remains challenging in the energy conversion and storage field. Metal–organic frameworks (MOFs) with a large specific surface area and a controllable pore structure provide a great opportunity to prepare bifunctional catalysts, but their low activity in oxygen electrocatalysis hinders their applications. Herein, we rationally design and fabricate a bimetallic ZnCo-zeolite imidazole framework@graphene oxide (ZnCo-ZIF@GO) hybrid electrocatalyst through a simple in situ growth of a bimetallic ZIF on graphene oxide nanosheets. The obtained ZnCo-ZIF@GO hybrid displays superior electrocatalytic activities toward both the ORR and OER in alkaline solution compared to the pure ZnCo-ZIF. The outstanding bifunctional electrocatalytic performance is attributed to the synergy and strong interaction between the ZnCo-ZIF and GO, enhanced ionic conductivity, and hierarchical porosity. A rechargeable Zn–air battery (ZAB) assembled using ZnCo-ZIF@GO as the air cathode displays excellent charge and discharge performance, high energy density, and cycling stability, demonstrating its great potential as an advanced bifunctional electrocatalyst in the field of energy conversion and storage.